Decreasing sunbed use in the German population between 2001 and 2015: survey in 155 679 working persons. (4th March 2019) - Augustin, M.; Schäfer, I.; Krensel, M.; Reusch, M.; Mohr, P.; Greinert, R.; John, S.M.; Zander, N.
Abstract: Background: UV radiation is a proven cause of skin cancer. Use of sunbeds has been shown to provide an attributable risk. Objective: To evaluate the proportion of regular sunbed use in Germany based on large‐scale population‐based surveys over 15 years. Methods: Skin cancer screenings by dermatologists were conducted between 2001 and 2015 in more than 500 German companies, including a clinical examination and interviews on the risk behaviour related to sunburns and sunbeds. Results: Among 155 679 persons included regular sunbed use significantly declined from 11.0% in 2001 to 1.6% in 2015 ( P < 0.001). There were significantly higher rates of sunbed use in women (12.5%/2.0%) vs. men (7.3%/1.3%; P < 0.001), in younger persons and in participants with darker skin (type II and III) vs. fair skin (type I). Individuals with sunburns in childhood were significantly more often sunbed users (5.1% vs. 4.6%; P = 0.002). A remarkable decline of sunbed use was observed after 2009 (7.0% in 2001–2008 and 2.2% in 2009–2015). This reduction occurred in the time of a legal ban of sunbed use for minors but also with the start of the national skin cancer screening programme. Conclusion: Use of sunbeds in the German adult population has dropped by more than 85% in the past decade. Primary prevention, including the large public awareness following the legal ban of sunbed use for young people and the effects of the statutory skin cancer screening programme may have contributed to this.